(untitled) (LACCEI, 2024)
Energy is of value for the inhabitants of a country and this is contemplated in the objectives of sustainable development. Considering the importance of this resource, it is necessary to choose the best alternatives in terms of equipment in energy substations. In this research, the GIS system was compared to the AIS, determining its advantages in technical and economic criteria: operation and maintenance, reliability within an energy system, implementation and installation costs. Considering a mixed approach and a concurrent nested design of several groups, three data collection techniques were applied, finding valuable information that allowed concluding that the SF6-encapsulated cell (GIS) presents greater advantages in space saving, reliability, space, and operation and maintenance.